(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The study’s goal is to examine how a training program affects the development of a weaver’s skills. Handloom training programs are necessary for the advancement and upgradation of weaving techniques (Balakrishnan & Nadu, 2019). Handloom is the traditional cottage industry of Orissa and is performed by weavers for generations to earn a livelihood with self employment. Skill has a multilevel role to play in the handloom industry, whether it’s learning to weave or utilising technology to boost weaving output. Due to the present advancement in technology, this industry is facing stiff completion in the market for substances. To overcome the situation, market-oriented products with colour fastness are required which can be done with skills training for the weavers. For this, data have been collected from 110 trained weavers who have undergone handloom training in Bargarh District. Paired Sample t-test was used to analyse the collected data, and Cohen’s D Test was used to calculate the effect size. The study discovered that after completing the training programme, the weavers’ skills significantly improved.